The Effectiveness of Problem-Based Learning (PBL) Model Assisted by Treasure Hunt Game on Students' Conceptual Understanding and Learning Interest in Grade II - Dina Aryanti; Firman; Syafri Ahmad; Melva Zainil (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model assisted by a treasure hunt game on conceptual understanding and interest in learning mathematics in Grade II elementary school students. This study used a quasi-experimental method with a non-equivalent control group design involving 21 students in the experimental class and 19 students in the control class. Data were collected using a pretest–posttest instrument for conceptual understanding and a questionnaire for learning interest. Data analysis included normality and homogeneity tests, followed by dependent and independent sample t-tests, and N-gain score tests using SPSS version 16.00. The results showed that the implementation of PBL assisted by a treasure hunt game had a positive and significant effect on conceptual understanding and interest in learning mathematics in Grade II elementary school students. Students in the experimental class obtained higher posttest scores and N-gain scores compared to students in the control class who received conventional learning. Thus, PBL integrated with treasure hunt game activities can be considered an effective learning approach to improve conceptual understanding and interest in learning mathematics in early-grade elementary students.